P683 Higher serum golimumab concentrations are significantly associated with combined clinical-biochemical remission during maintenance therapy: results from the GO-LEVEL study. (25th January 2019) - Samaan, M; Cunningham, G; Tamilarasan, A G; Rawstron, K; Hawash, K; Beltran, L; Koumoutsos, I; Ray, S; Mawdsley, J; Anderson, S; Sanderson, J; Arkir, Z; et al.
Abstract: Background: The exposure–response relationship associated with the use of golimumab for UC has been previously demonstrated in the PURSUIT trials. A significant association between serum golimumab concentrations (SGC) and favourable outcomes were observed during both induction and maintenance therapy. Methods: GO-LEVEL was an open-label, phase IV study (NCT03124121) which included a prospective cohort commencing induction therapy as well as a cross-sectional cohort of patients receiving maintenance treatment (defined as a minimum of 18 weeks from initiation). Here we report the results of the maintenance study. Patients receiving maintenance therapy were recruited either at the point of flare, or during stable remission. Clinical disease activity was evaluated using SCCAI and PRO2, biochemical activity using faecal calprotectin (FC) and CRP and QoL using the IBD-Control questionnaire. Clinical remission was defined as SCCAI < 3. Combined clinical-biochemical remission was defined as SCCAI < 3 as well as FC < 250 μg/g. SGC and anti-golimumab antibodies (AGA), measured using a drug-sensitive ELISA (LISA-TRACKER, Theradiag). Samples were collected within 7 days of the subsequent administration. Fishers Exact or Mann–Whitney U were used to compare groups and ROC analysis to identify therapeutic threshold. Results: In total, 49 patients on maintenance treatment were recruited; 31 in clinical remission and 18 at the point of flare. There was no significant difference in median SGC between the two groups (2.7 vs. 2.1 μg/ml, respectively, p = 0.27). Of the 46 patients with FC data available, 24 were in combined remission, 22 were not. The median SGC of those in combined remission was significantly higher than those who were not (3.0 vs. 2.0 μg/ml, respectively, p = 0.031). Univariate analysis comparing groups can be seen in Table 1. No AGA were detected. Univariate analysis of comparing characteristics, disease activity evaluations, quality of life and golimumab levels of patients in combined clinical-biochemical remission with those who were not. ROC curve analysis demonstrates 2.1 μg/ml as the optimal therapeutic threshold for combined remission (sens 0.75, spec 0.59, AUC 0.69). ROC curve analysis of optimal SGC thresholds associated with combined clinical-biochemical remission. Conclusions: The GO-LEVEL maintenance cohort offers further evidence of the exposure–response relationship with golimumab, particularly when using a combined definition of remission that includes an objective marker of disease activity (FC). Clinicians may consider using therapeutic drug monitoring to optimise golimumab dosing aiming to achieve our suggested therapeutic threshold of 2.1 μg/ml.